THE EXPERIENCES OF INTERNATIONAL STUDENTS AT THE UNIVERSITY OF THE WITWATERSRAND - Namyalo, Rosemary (My University, 2013)
Literature shows that international students experience challenges as they move from one country to another in pursuit of education. This is because there is a high demand for higher education worldwide. Higher education institutions need to recognize that international students need to be supported. The University of The Witwatersrand has managed to attract international postgraduate students from Africa, Asia, North America, Europe and Australia. The purpose of this exploratory study is to investigate the challenges experienced by international postgraduate students and factors that lead to those challenges. The exploratory study is qualitative in nature. Primary data was collected using in-depth interviews (one-on-one), online journals and documents from the University of The Witwatersrand to guide the literature review. The findings showed that International Postgraduate Students experience challenges in areas of; accommodation, financial constraints, supervision, registration progress and adjusting to the new academic system. The researcher found that International Postgraduate students are provided with the following services; library services, accommodation services, medical services and bus services. However, participants expressed disappointment in some of the services like the medical and accommodation services. The researcher found that a good number of International Postgraduate Students were satisfied with the library services. A number of theories were used in this study that assisted in aligning policies with student services to make them more efficient and accessible. The organisation, systems and student service theory in practice guided the study.
MM (P&DM) thesis
Keywords: International students; Universities and international students